Pengaruh Penerimaan Pajak dan Inflasi Terhadap Pertumbuhan Ekonomi di Indonesia - Indah Zahara; Khairul Amri (Jurnal Ekonomi Manajemen dan Sekretari, 2024)
The aim of this research is to analyze the relationship between tax revenues and inflation on economic growth. Using annual time series data from the 2000-2019 period. The research method used is multiple linear regression and autoregressive distribution lag (ARDL). The research results show that there is a cointegration relationship between economic growth and tax revenues and inflation. Using a multiple linear regression analysis model states that tax revenues and inflation have a positive and insignificant effect on economic growth. Furthermore, using autoregressive distribution lag (ARDL) analysis states that tax revenues have an insignificant negative effect in the long term, while in the short term tax revenues have a positive and significant effect on economic growth. Inflation has an insignificant negative effect on economic growth in the long term, but in the short term inflation has a significant negative effect on economic growth. This finding has the implication that efforts to increase economic growth can be made by keeping taxes and inflation levels at a stable level.